Penyuluhan Dampak Mental Kekerasan Rumah Tangga Di Kecamatan Kerambitan Kabupaten Tabanan - Paramitha, Ni Made Ayu Susanthi Pradnya; Arini, Ni Wayan; Kantriani, Ni Ketut; Swarthini, Ni Nyoman Ayu; Kartika, Luh Gede Surya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Domestic violence is a common problem that affects individuals of different ages, social backgrounds, and economic circumstances. This includes a wide range of economic, sexual, emotional, and physical violent behaviors that occur in close relationships, such as marriage or family connections. This counseling activity will be carried out in Tista Village, Tabanan Regency in May 2023. Domestic violence counseling seeks to increase understanding of the psychological impact of domestic violence on people, especially victims and perpetrators of domestic violence, as well as society. The purpose of this outreach is to educate the public, especially victims, about the psychological impact of domestic violence, such as anxiety, grief, PTSD, and other psychological problems. In addition, the public is taught about the need to prevent domestic violence and specific prevention methods to reduce its impact. This outreach initiative seeks to help educate the perpetrators of domestic violence to be able to modify their behavior by explaining the negative psychological implications of their actions. The results of the final observations show that there are still many opportunities for similar activities that are necessary and important to be carried out to reduce the number and impact of domestic violence.